The novel HLA‐A*24:520 allele was identified in a Chinese individual. (3rd August 2022) - Zhu, Jianrong; Hu, Wenjian; Fu, Guangchen; Chen, Yujuan; Zhu, Faming
Abstract : HLA‐A*24:520 differs from HLA‐A*24:02:01:01 by one nucleotide substitution at position 668 C→T in exon 4.